A Discourse of Justice and Legal Certainty in Stolen Assets Recovery in Indonesia: Analysis of Radbruch’s Formula and Friedman’s Theory - Arifin, Ridwan; Wulandari, Cahya; Muliadi, Muliadi; Utari, Indah Sri; Munandar, Tri Imam (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
This paper critically examines stolen assets recovery in Indonesia, employing Gustav Radbruch's legal philosophy, which asserts that justice is the purpose of law and any rule failing to promote justice is invalid, along with Lawrence Friedman’s sociological theory. The aim is to illuminate Indonesia's challenges and opportunities in recovering ill-gotten assets, an issue intertwined with corruption, transnational crime, and international cooperation. Radbruch’s formula serves as the moral and ethical basis for evaluating asset recovery. It prioritizes justice in legal systems, insisting that just laws are the only legitimate ones. This paper applies Radbruch’s formula to assess Indonesia's legal frameworks and processes for asset recovery, emphasizing principles like fairness, equity, and legitimacy within this context. Furthermore, this study incorporates Friedman’s sociological theory, which examines how law evolves in response to social norms and values. It explores how sociocultural factors in Indonesia influence the development of legal mechanisms, public attitudes, and enforcement strategies regarding asset recovery. These perspectives offer valuable insights into Indonesia’s asset recovery challenges. They underscore the need for a holistic approach that integrates ethics, law, and sociology to enhance fairness and effectiveness. International collaboration is also emphasized due to the transnational nature of illicit financial flows. This paper contributes to a nuanced examination of Indonesia’s stolen assets recovery. By bridging legal philosophy and sociological theory, it provides a comprehensive framework for policymakers, legal professionals, and scholars engaged in pursuing justice and asset recovery in Indonesia and beyond.